Analysis The Ability of Students Problem-Solving on Counting Operations of Algebra Form - Desy Yusnia (MUST: Journal of Mathematics Education, Science and Technology, 2018)
Problem-solving is the important part of mathematics curriculum. Most of students still have difficulties and error in prombelm solving. This research aims to know problem-solving ability of students on counting operations of algebra form. This research is a descriptive qualitative research. The subject is students grade VII-F SMP N 1 Wonosari. The data collecting technique is a problem-solving test. The data analysis according to Miles and Huberman, which is data reduction, data presentation, and making the conclusion. The results of this research showing that: (1) 95.56% of students can understand the problem, 4.44% of students cannot understand the problem; (2) 18.33% of students can devising a plan, 81.67% cannot devising a plan; (3) 28.61% of students can carrying out the plan, 71.39% cannot carrying out the plan; (4) 45% can looking back the answer, 55% cannot looking back the answer.